Sustainability of Intraocular Pressure Reduction of Travoprost Ophthalmic Solution in Subjects with Normal Tension Glaucoma. Issue 3 (March 2016) - Naito, Tomoko; Okuma, Shinichi; Nagayama, Mikio; Mizoue, Shiro; Ozaki, Mineo; Namiguchi, Koji; Miyamoto, Kazuhisa; Tanito, Masaki; Yoshikawa, Keiji
Abstract Introduction We examined the sustainability of the intraocular pressure (IOP)-lowering efficacy of travoprost (0.004%) ophthalmic solution in subjects with normal tension glaucoma (NTG). Methods Travoprost ophthalmic solution was given once daily at 9 PM to subjects with newly diagnosed NTG or with NTG who had not received any ocular hypotensives within the previous 30 days. IOP was measured at three time points (9 AM, 1 PM, and 5 PM) at baseline and week 12 visits, and at one time point (9 AM) at week 4 and week 8 visits. Conjunctival hyperemia, superficial punctate keratopathy, and other adverse events were evaluated during the observation period. Results Thirty subjects (12 males and 18 females; mean age 65.6 years) from 32 subjects enrolled were included in the efficacy analysis. The mean IOPs (±standard deviation) of 16.6 ± 1.4, 15.7 ± 1.8, and 15.7 ± 2.2 mmHg at 9 AM, 1 PM, and 5 PM, respectively, at baseline reduced significantly to the mean IOPs of 13.0 ± 1.8, 12.7 ± 1.8, and 12.8 ± 1.6 mmHg, respectively, at week 12 (P  < 0.0001 for every time point). Together with the mean IOPs of 13.4 ± 1.9 mmHg at week 4 and 13.2 ± 1.9 mmHg at week 8, the pooled IOP during the observation period for up to 12 weeks showed a statistically and clinically significant reduction of IOP at 9 AM. (3.4 mmHg or 20.3% reduction from baseline, P  < 0.0001). There were no adverse events leading to treatment discontinuation. Conclusion This multi-center collaborative study suggests that IOP-lowering efficacy of travoprost ophthalmic solution persists during the day at the clinically relevant level in subjects with NTG. Funding Alcon Japan Ltd. Trial registration University Hospital Medical Information Network, UMIN ID: 000011621.